Knowledge and factors affecting initiation of breast feeding in post-natal mothers in a tertiary care center - Gavhane, Sunil; Yadav, Sudha; Uday, Kanumala; Kale, Anjali; Sirohi, Aniket; Yadav, Pawan; Jadhao, Pranoti (International Journal of Research in Medical Sciences, 2018)
Background: The study was planned to evaluate awareness of breast feeding among mother, institutional quality indicators of early breast feeding. The objective was to know factors causing delay in breast feeding initiation, to assess knowledge, cultural practices, and quality indicators of hospital regarding breast feeding initiative. Methods: The observational study was conducted over a period of 3months from July 2017-Sept 2017 in a tertiary care centre of India. 118 postnatal mothers were interviewed for time of first breast feeding (dependent variable or outcome), and independent variables age, education , religion, parity, occupation of mother, antenatal visits, prelacteal feeds, customs of not breast feeding, duration of labour, mode of delivery, sedation, pain after delivery, baby over mother abdomen after birth, institutional quality indicators-knowledge of breast feeding given by doctor /nurses, relatives, self reading, mothers with correct attachment and position of baby during breast feeding and separation of mother and baby post delivery. Results: Mean time of initiation of breast feeding was 1340.262min after birth. Prelacteal feeds, lack of education, cesarean deliveries, parity of mother, sedation, anesthesia during cesarean and lack of counselling by staff nurses were found to have early increased time of initiation of breast feeding. Conclusions: Great lacuna in knowledge, attitude and practice of early breast feeding of mother.